Ethylene / alpha-olefin interpolymer compositions with high glass adhesion
The ethylene/α-olefin interpolymer composition with Si-containing compounds addresses adhesion and resistivity issues in photovoltaic encapsulation films, ensuring robust protection for solar cells under high temperature and humidity.
Patent Information
- Application Number
- CN202411323082.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2019-12-26
- Publication Date
- 2024-12-31
AI Technical Summary
Existing photovoltaic encapsulation films, primarily based on ethylene vinyl acetate (EVA), suffer from issues such as acid release leading to solar cell corrosion, low volume resistivity causing potential induced degradation, and inadequate adhesion to glass, especially under high temperature and humidity conditions.
A composition comprising ethylene/α-olefin interpolymer, peroxides, and Si-containing compounds, particularly vinyl oligomeric siloxanes, is used to enhance adhesion to glass and maintain high volume resistivity, with optional additives like hindered amines and cross-linking agents to improve curing properties.
The composition provides strong adhesion to glass, maintains high volume resistivity, and ensures good curing properties, effectively protecting solar cells from corrosion and degradation under harsh conditions.
Smart Images

Figure BDA0005054560690000034 
Figure BDA0005054560690000052 
Figure BDA0005054560690000102
Abstract
Description
[0001] This application is a divisional application based on a patent application with an application date of December 26, 2019, application number 2019801032316, and invention name “Ethylene / α-olefin interpolymer composition with high glass adhesion”. Background Art
[0002] Due to the shortage and non-renewability of fossil fuel resources, and the need to reduce environmental pollution, the demand for solar cell modules has increased. Solar cell modules typically include a front side protective material (usually a glass plate), a front side sealant, a solar cell array, a rear side sealant, and a back side protective material (which can be a backsheet or a glass plate). Solar cells convert solar energy into electrical energy and are extremely fragile. If water penetrates into the module, these cells become corroded. The sealant is designed to protect the cell array from humidity, mechanical loads, and impacts. In addition, the sealant provides electrical isolation to prevent current loss. The sealant provides mechanical protection and some UV stability and must have good adhesion to the glass and / or backsheet.
[0003] The requirements of the sealant require that the polymer composition used to form the encapsulation film (photovoltaic (PV)) has good lamination properties to provide sufficient adhesion to glass, solar cell arrays and backsheets. In addition, the film must have good electrical insulation, low water vapor permeability and good optical transparency. Current photovoltaic encapsulation films are mainly made of compositions based on ethylene vinyl acetate (EVA). See, for example, US2013 / 0324671 and CN106189932A. However, EVA will release acid during use, which will corrode solar cells and ribbon solder over time. In addition, due to the low volume resistivity (VR) of EVA, the greater the possibility of potential induced degradation in the encapsulation. Therefore, it is necessary to have and maintain strong adhesion, especially a polymer composition with strong adhesion to glass, and have a high volume resistivity.
[0004] CN106414592A discloses a sealing film for solar cells, and it is formed by "metallocene-catalyzed" ethylene / α-olefin copolymer, organic peroxide, silane coupling agent and magnesium hydroxide or magnesium oxide. Magnesium hydroxide or magnesium oxide prevents the formation of adhesion during storage by preventing the peroxide and coupling agent from bleeding, hydrolysis and gelation. However, magnesium hydroxide or magnesium oxide may deteriorate the transparency of the encapsulation film. Additional polyolefin-based compositions and other compositions for solar cell modules are described in CN105950039A; CN106811150A and CN104263258A.
[0005] However, as discussed, there remains a need for polymer compositions that have and maintain strong adhesion, especially to glass, in the form of initial laminates and after high temperature and high humidity aging, and also have high volume resistivity. These needs have been met by the following invention. Summary of the invention
[0006] A composition comprising:
[0007] a) ethylene / α-olefin / interpolymer;
[0008] b) peroxides;
[0009] c) "Si-containing compounds" selected from the following i) to v):
[0010] i)
[0011] wherein each R is independently selected from C1-C3 alkyl, and n is 1 to 16;
[0012] ii)
[0013] wherein each R is independently methyl or ethyl, and n is 1 to 18;
[0014] iii)
[0015] wherein each R is independently methyl or ethyl;
[0016] iv) vinyl oligosiloxane; or
[0017] v) Any combination of i) to iv).
[0018] The present invention comprises:
[0019] 1. A composition comprising:
[0020] a) ethylene / α-olefin / interpolymer;
[0021] b) peroxides;
[0022] c) "Si-containing compounds" selected from the following i) to v):
[0023] i)
[0024] wherein each R is independently selected from C1-C3 alkyl, and n is 1 to 16;
[0025] ii)
[0026] Each R is independently methyl or ethyl, and n is from 1 to 18;
[0027] iii)
[0028] where each R is independently methyl or ethyl;
[0029] iv) Vinyl oligomeric siloxane; or
[0030] v) Any combination of i) to iv).
[0031] 2. The composition according to item 1, wherein the "Si-containing compound" (component c) is selected from the following i) to v):
[0032]
[0033] iv) Vinyl oligomeric siloxane; or v) Any combination of i) to iv).
[0034] 3. The composition according to item 1, wherein the "Si-containing compound" is selected from the following:
[0035] iv) Vinyl oligomeric siloxane.
[0036] 4. The composition according to item 3, wherein the "Si-containing compound" is a vinyl oligomeric siloxane comprising at least two different compounds selected from the following formula 4A:
[0037] iv) R1 x R2 y R3 z Si n O m (Formula 4A), where R1 is vinyl, x is greater than or equal to (≥) 1, R2 is propyl, y is greater than or equal to (≥) 0 and less than or equal to (≤) 1, R3 is ethoxy or methoxy, z = 4n - x - y - m, 1 < n < 10, and m ≤ n - 1.
[0038] 5. The composition according to item 1, wherein the "Si-containing compound" is selected from the following:
[0039] i)
[0040] where each R is independently selected from C1-C3 alkyl, and n is from 1 to 16;
[0041] ii)
[0042] where each R is independently methyl or ethyl, and n is from 1 to 18;
[0043] iii)
[0044] wherein each R is independently methyl or ethyl; or
[0045] v) Any combination of i) to iii).
[0046] 6. The composition according to item 1, wherein the "Si-containing compound" is selected from the following:
[0047] ii)
[0048] wherein each R is independently methyl or ethyl, and n is 1 to 18;
[0049] iii)
[0050] wherein each R is independently methyl or ethyl; or
[0051] v) A combination of ii) and iii).
[0052] 7. The composition according to item 6, wherein the "Si-containing compound" is selected from the following:
[0053] or
[0054] vi) A combination of ii) and iii).
[0055] 8. The composition according to item 6 or item 7, wherein the "Si-containing compound" is selected from the combination of ii) and iii).
[0056] 9. The composition according to item 8, wherein the weight ratio of component iii) to component ii) is ≥ 2.0.
[0057] 10. The composition according to item 8 or item 9, wherein the weight ratio of component iii) to component ii) is ≤ 4.0.
[0058] 11. The composition according to item 1, wherein the "Si-containing compound" is selected from the following:
[0059] i)
[0060] wherein each R is independently selected from C1-C3 alkyl, and n is 1 to 16.
[0061] 12. The composition according to item 11, wherein the "Si-containing compound" is selected from the following:
[0062] i)
[0063]
[0064] 13. The composition according to any one of the preceding items, wherein the composition further comprises an adjuvant.
[0065] 14. The composition according to any of the preceding items, wherein the weight ratio of the peroxide to the "Si-containing compound" is ≥ 1.0.
[0066] 15. The composition according to any of the preceding items, wherein the weight ratio of the peroxide to the "Si-containing compound" is ≤ 6.0.
[0067] 16. The composition according to any of the preceding clauses, wherein the composition further comprises a hindered amine.
[0068] 17. The composition of any of the preceding items, wherein the composition comprises ≥ 50.0 wt% of the ethylene / α-olefin interpolymer (component a), based on the weight of the composition.
[0069] 18. The composition according to any of the preceding clauses, wherein the composition comprises ≥ 98.5 wt% of the sum of components a) - c) based on the weight of the composition.
[0070] 19. The composition of any of the preceding items, wherein for the ethylene / α-olefin interpolymer, the α-olefin is a C3-C20 α-olefin.
[0071] 20. The composition according to any of the preceding items, wherein the ethylene / α-olefin interpolymer (component a) is an ethylene / α-olefin copolymer.
[0072] 21. The composition according to any of the preceding items, wherein the density of the ethylene / α-olefin interpolymer (component a) is ≥ 0.860 g / cc (1 cc = 1 cm 3 ).
[0073] 22. The composition of any of the preceding items, wherein the ethylene / α-olefin interpolymer has a density of ≤ 0.900 g / cc.
[0074] 23. The composition according to any of the preceding items, wherein the ethylene / α-olefin interpolymer (component a) has a melt index (I2) of ≥ 8.0 g / 10 min.
[0075] 24. The composition according to any of the preceding items, wherein the ethylene / α-olefin interpolymer has a melt index (I2) of ≤ 35 g / 10 min.
[0076] 25. A cross-linked composition formed from the composition according to any one of the preceding items.
[0077] 26. The composition according to any of the preceding items, wherein the composition has a peel adhesion strength of ≥ 90 N / cm.
[0078] 27. The composition according to any one of the preceding items, wherein the composition has a glass adhesion strength of ≥ 70 N / cm after aging at 85°C and 85% humidity for 1000 h.
[0079] 28. The composition according to any one of the preceding items, wherein the volume resistivity of the composition is ≥1.0×10 14 ohm·cm.
[0080] 29. The composition according to any one of the preceding items, wherein the volume resistivity of the composition is ≥1.0×10 17 ohm·cm.
[0081] 30. An article comprising at least one component formed from a composition according to any of the preceding items.
[0082] 31. The article of claim 30, wherein the article is a film.
[0083] 32. The article of claim 30, wherein the article is a solar cell module.
[0084] 33. A method of forming a solar cell module, the method comprising laminating a "solar cell array" between two film layers, and wherein each film layer is independently formed from a composition according to any one of items 1 to 29. BRIEF DESCRIPTION OF THE DRAWINGS
[0085] Figure 1 Depicted are schematic diagrams of a cross section of a laminate (left), a test sample for adhesion peel testing (as described on the laminate) (center), and the test sample configuration during adhesion peel testing (right). DETAILED DESCRIPTION
[0086] In laminated solar cell modules, it is necessary to have high bond strength between the sealing film and the front glass layer. Compositions have been found that provide and maintain the required high bond strength. In addition, these compositions have high volume resistivity and good curing properties.
[0087] As discussed above, there is provided a composition comprising:
[0088] a) ethylene / α-olefin / interpolymer;
[0089] b) peroxides;
[0090] c) "Si-containing compounds" selected from the following i) to v):
[0091] i)
[0092] wherein each R is independently selected from C1-C3 alkyl or C1-C2 alkyl or C1 alkyl; and n is 1 to 16, or 1 to 14, or 1 to 12, or 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4;
[0093] ii)
[0094] wherein each R is independently methyl or ethyl or methyl; and n is 1 to 18, or 1 to 16, or 1 to 14, or 1 to 12, or 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4, or 1 to 3;
[0095] iii)
[0096] wherein each R is independently methyl or ethyl or ethyl;
[0097] iv) vinyl oligosiloxane; or
[0098] v) Any combination of i) to iv).
[0099] Vinyl oligosiloxanes contain multiple (≥2) chemical molecules (or compounds) that differ only in molecular weight and wherein each molecule (or compound) contains at least one vinyl group and at least one siloxane group. All of these similar molecules may be linear, branched or cyclic.
[0100] In one embodiment or a combination of two or more embodiments described herein individually, the "Si-containing compound" (component c) is selected from the following i)
[0101] to v):
[0102] Vinyl oligosiloxane iv); or v) any combination of i) to iv).
[0103] In one embodiment or a combination of two or more embodiments each described herein, the "Si-containing compound" is selected from the following:
[0104] iv) Vinyl oligosiloxane.
[0105] In one embodiment or a combination of two or more embodiments each described herein, the "Si-containing compound" is a vinyl oligosiloxane comprising at least two different compounds selected from the following formula 4A:
[0106] iv) R1 x R2 y R3z Si n O m (Formula 4A), where R1 is vinyl, x is greater than or equal to (≥) 1, R2 is propyl, y is greater than or equal to (≥) 0 and less than or equal to (≤) 1, R3 is ethoxy or methoxy, z = 4n - x - y - m, 1 < n < 10, and m ≤ n - 1.
[0107] In one embodiment described herein or in a combination of two or more embodiments, the "Si-containing compound" is selected from the following:
[0108] i)
[0109] where each R is independently selected from C1-C3 alkyl or C1-C2 alkyl or C1 alkyl; and n is from 1 to 16, or 1 to 14, or 1 to 12, or 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4;
[0110] ii)
[0111] where each R is independently methyl or ethyl or methyl; and n is from 1 to 18, or 1 to 16, or 1 to 14, or 1 to 12, or 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4, or 1 to 3;
[0112] iii) where each R is independently methyl or ethyl or ethyl; or
[0113] v) Any combination of i) to iii).
[0114] In one embodiment described herein or in a combination of two or more embodiments, the "Si-containing compound" is selected from the following:
[0115] ii)
[0116] where each R is independently methyl or ethyl or methyl; and n is from 1 to 18, or 1 to 16, or 1 to 14, or 1 to 12, or 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4, or 1 to 3;
[0117] iii)
[0118] where each R is independently methyl or ethyl or ethyl; or
[0119] v) A combination of ii) and iii).
[0120] In one embodiment described herein or in a combination of two or more embodiments, the "Si-containing compound" is selected from the following:
[0121] Or a combination of v) ii) and iii).
[0122] In one embodiment or a combination of two or more embodiments individually described herein, the "Si-containing compound" is selected from the combination of ii) and iii).
[0123] In one embodiment or a combination of two or more embodiments described herein, the weight ratio of component iii) to component ii) is ≥2.0, or ≥2.2, or ≥2.4, or ≥2.6, or ≥2.8, or ≥3.0. In one embodiment or a combination of two or more embodiments described herein, the weight ratio of component iii) to component ii) is ≤4.0, or ≤3.8, or ≤3.6, or ≤3.4, or ≤3.2.
[0124] In one embodiment or a combination of two or more embodiments each described herein, the "Si-containing compound" is selected from the following:
[0125] i)
[0126] wherein each R is independently selected from C1-C3 alkyl or C1-C2 alkyl or C1 alkyl; and n is 1 to 16, or 1 to 14, or 1 to 12, or 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4.
[0127] In one embodiment or a combination of two or more embodiments each described herein, the "Si-containing compound" is selected from the following:
[0128] i)
[0129]
[0130] In one embodiment or a combination of two or more embodiments described herein,
[0131] The "Si-containing compound" is selected from the following:
[0132] ii)
[0133] wherein each R is independently methyl or ethyl or methyl; and n is 1 to 18, or 1 to 16, or 1 to 14, or 1 to 12, or 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4, or 1 to 3.
[0134] In one embodiment or a combination of two or more embodiments each described herein, the "Si-containing compound" is selected from the following:
[0135] ii)
[0136]
[0137] In one embodiment or a combination of two or more embodiments each described herein, the "Si-containing compound" is selected from the following:
[0138] iii)
[0139] wherein each R is independently methyl or ethyl or ethyl;
[0140] In one embodiment or a combination of two or more embodiments each described herein, the "Si-containing compound" is selected from the following:
[0141] iii)
[0142] Crosslinking aids promote crosslinking reactions within the polymer composition. Auxiliary agents include, but are not limited to, triallyl isocyanurate, triallyl cyanurate and trimethylolpropane trimethacrylate, divinylbenzene, acrylates and methacrylates of polyols, allyl alcohol derivatives, and low molecular weight polybutadiene.
[0143] In one embodiment or a combination of two or more embodiments described herein, the composition further comprises an adjuvant. In one embodiment or a combination of two or more embodiments described herein, the weight ratio of peroxide to adjuvant composition is ≥0.5, ≥0.8, ≥1.0, or ≥1.2, or ≥1.4, or ≥1.6, or ≥1.8, or ≥2.0. In one embodiment or a combination of two or more embodiments described herein, the weight ratio of peroxide to adjuvant composition is ≤3.0, or ≤2.8, or ≤2.6, or ≤2.4, or ≤2.2.
[0144] The peroxide (containing at least one "-OO-" group) is preferably an organic peroxide, such as tert-butyl peroxy 2-ethylhexyl carbonate; di-tert-butyl peroxide; tert-butyl isopropyl peroxide; diisopropyl peroxide; 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane; di(tert-butylperoxyisopropyl)benzene peroxybenzoate; 1,1-di(tert-butylperoxy)-3,3,5-trimethyl-cyclohexane; alkane; 2,5-dimethyl-2,5-di(tert-amyl peroxy)hexane; 2,5-dimethyl-2,5-di(tert-butyl peroxy)hexyne-3, 2,5-dimethyl-2,5-di(tert-amyl peroxy)hexyne-3; di-tert-amyl peroxide; 1,3-dimethyl-3-(tert-butyl peroxy)butanol; 1,3-dimethyl-3-(tert-amyl peroxy)butanol; and mixtures of two or more of these initiators. See, for example, TRIGONOX peroxide from AkzoNobel, LUPEROX peroxide from ARKEMA.
[0145] In one embodiment or a combination of two or more embodiments described herein, the weight ratio of peroxide to "Si-containing compound" is ≥1.0, or ≥1.5, ≥2.0, or ≥2.2, or ≥2.4, or ≥2.6, or ≥2.8, or ≥3.0, or ≥3.2, or ≥3.4, or ≥3.6, or ≥3.8, or ≥4.0. In one embodiment or a combination of two or more embodiments described herein, the weight ratio of peroxide to "Si-containing compound" is ≤6.0, or ≤5.8, or ≤5.6, or ≤5.4, or ≤5.2, or ≤5.0, or ≤4.8, or ≤4.6, or ≤4.4, or ≤4.2.
[0146] Hindered amine light stabilizers (HALS) are chemical compounds containing amine functional groups and are used as stabilizers in polymer compositions. The nitrogen atom of the amine is partially shielded by adjacent groups to reduce the possibility of side reactions with the nitrogen atom. Hindered amines include, but are not limited to, TINUVIN 770 (bis-(2,2,6,6-tetramethyl-4-piperidinyl) sebacate), CYASORB UV3529, HOSTAVIN N30, UNIVIL 4050, UNIVIN 5050, CHIMASSORB UV 119, CHIMASSORB 944LD, and TINUVIN 622LD.
[0147] In one embodiment or a combination of two or more embodiments described herein, the composition further comprises a hindered amine light stabilizer. In one embodiment or a combination of two or more embodiments described herein, the weight ratio of the "Si-containing compound" to the hindered amine is ≥1.0, ≥2.0, ≥3.0, or ≥3.1, or ≥3.2, or ≥3.3, or ≥3.4, or ≥3.5. In one embodiment or a combination of two or more embodiments described herein, the weight ratio of the "Si-containing compound" to the hindered amine is ≤7.0, or ≤6.8, or ≤6.6, or ≤6.4, or ≤6.2, or ≤6.0.
[0148] In one embodiment or a combination of two or more embodiments described herein, the composition comprises ≥50.0 wt%, ≥60.0 wt%, or ≥70.0 wt%, or ≥80.0 wt%, or ≥90.0 wt% of the ethylene / α-olefin interpolymer (component a), based on the weight of the composition. In one embodiment or a combination of two or more embodiments described herein, the composition comprises ≥95.0 wt%, or ≥95.5 wt%, or ≥96.0 wt%, or ≥96.5 wt%, or ≥97.0 wt%, or ≥97.5 wt%, or ≥98.0 wt% of the ethylene / α-olefin interpolymer (component a), based on the weight of the composition.
[0149] In one embodiment or a combination of two or more embodiments individually described herein, the composition comprises ≤99.8 wt%, ≤99.6 wt%, or ≤99.4 wt%, or ≤99.2 wt%, or ≤99.0 wt%, or ≤98.8 wt%, or ≤98.6 wt%, or ≤98.4 wt%, or ≤98.2 wt% of the ethylene / α-olefin interpolymer (component a), based on the weight of the composition.
[0150] In one embodiment or a combination of two or more embodiments described herein, the composition comprises ≥98.5 wt%, or ≥99.0 wt%, or ≥99.1 wt%, or ≥99.2 wt%, or ≥99.3 wt%, or ≥99.4 wt% of the sum of components a)-c), based on the weight of the composition. In one embodiment or a combination of two or more embodiments described herein, the composition comprises ≤100.0 wt%, or ≤99.9 wt%, ≤99.8 wt%, or ≤99.7 wt%, or ≤99.6 wt%, or ≤99.5 wt% of the sum of components a)-c), based on the weight of the composition.
[0151] In one embodiment or a combination of two or more embodiments each described herein, for the ethylene / α-olefin interpolymer (component a), the α-olefin is a C3-C20 α-olefin, and further a C3-C10 α-olefin. In one embodiment or a combination of two or more embodiments each described herein, the α-olefin is selected from propylene, 1-butene, 1-pentene, 1-hexene or 1-octene, and further propylene, 1-butene or 1-octene, and further 1-butene or 1-octene, and further 1-octene.
[0152] In one embodiment or a combination of two or more embodiments described herein, the ethylene / α-olefin interpolymer (component a) is an ethylene / α-olefin copolymer. In one embodiment or a combination of two or more embodiments described herein, the ethylene / α-olefin interpolymer (component a) is selected from the following: ethylene / propylene copolymers, ethylene / butene copolymers or ethylene / octene copolymers, and further ethylene / butene copolymers or ethylene / octene copolymers, and further ethylene / octene copolymers.
[0153] In one embodiment or a combination of two or more embodiments described herein, the ethylene / α-olefin interpolymer (component a) has a density of ≥ 0.860 g / cc, or ≥ 0.865 g / cc, or ≥ 0.868 g / cc, or ≥ 0.870 g / cc, or ≥ 0.872 g / cc, or ≥ 0.874 g / cc, or ≥ 0.876 g / cc, or ≥ 0.878 g / cc, or ≥ 0.880 g / cc (1 cc = 1 cm 3 In one embodiment or a combination of two or more embodiments individually described herein, the ethylene / α-olefin interpolymer has a density of ≤0.900 g / cc, or ≤0.898 g / cc, or ≤0.896 g / cc, or ≤0.894 g / cc, or ≤0.892 g / cc, or ≤0.890 g / cc, or ≤0.888 g / cc, or ≤0.886 g / cc, or ≤0.884 g / cc, or ≤0.882 g / cc.
[0154] In one embodiment or a combination of two or more embodiments described herein, the melt index (I2) of the ethylene / α-olefin interpolymer (component a) is ≥8.0 g / 10 min, or ≥10 g / 10 min, or ≥12 g / 10 min, or ≥14 g / 10 min, or ≥16 g / 10 min, or ≥18 g / 10 min. In one embodiment or a combination of two or more embodiments described herein, the melt index (I2) of the ethylene / α-olefin interpolymer is ≤35 g / 10 min, or ≤30 g / 10 min, or ≤28 g / 10 min, or ≤26 g / 10 min, or ≤24 g / 10 min, or ≤22 g / 10 min, or ≤20 g / 10 min.
[0155] The present invention also provides a cross-linked composition formed from the composition of any one embodiment or a combination of two or more embodiments described herein individually.
[0156] In one embodiment or a combination of two or more embodiments described herein, the glass adhesion strength of the composition is ≥90N / cm, or ≥92N / cm, or ≥94N / cm, or ≥96N / cm, or ≥100N / cm, or ≥110N / cm, or ≥120N / cm, or ≥130N / cm, or ≥140N / cm. In one embodiment or a combination of two or more embodiments described herein, the glass adhesion strength of the composition after aging for 1000h at 85C and 85% humidity is ≥70N / cm, or ≥75N / cm, or ≥80N / cm, or ≥85N / cm, or ≥90N / cm, or ≥95N / cm, or ≥100N / cm, or ≥105N / cm.
[0157] In one embodiment or a combination of two or more embodiments described herein, the volume resistivity of the composition is ≥1.0×10 14 ohm·cm, or ≥5.0×10 15 ohm·cm, ≥1.0×10 16 ohm·cm, or ≥2.0×10 16 ohm·cm, or ≥3.0×10 16 ohm·cm, or ≥4.0×10 16 ohm·cm, or ≥5.0×10 16 In one embodiment or a combination of two or more embodiments described herein, the volume resistivity of the composition is ≥1.0×10 17 ohm·cm, or ≥1.2×10 17 ohm·cm, or ≥1.4×10 17ohm·cm, or ≥1.6×10 17 ohm·cm, or ≥1.8×10 17 ohm·cm, or ≥1.9×10 17 ohm·cm.
[0158] The present invention also provides an article comprising at least one component formed by a composition of one embodiment or a combination of two or more embodiments described herein. In one embodiment or a combination of two or more embodiments described herein, the article is a film, and further an extruded film. In one embodiment or a combination of two or more embodiments described herein, the article is a solar cell module.
[0159] The present invention also provides a method for forming a solar cell module, the method comprising laminating a "solar cell array" between two film layers, and wherein each film layer is independently formed of a composition of any one embodiment or a combination of two or more embodiments described herein. In another embodiment, each film layer is formed of the same composition.
[0160] In one embodiment or a combination of two or more embodiments described herein, the composition of the present invention further comprises a thermoplastic polymer that differs from the interpolymer of component a) in one or more characteristics, such as monomer type and / or amount, Mn, Mw, Mz, MWD, Mooney viscosity, V0.1, V100, RR or any combination thereof. Polymers include, but are not limited to, ethylene-based polymers, propylene-based polymers, and olefin multi-block interpolymers. Suitable ethylene-based polymers include, but are not limited to, high density polyethylene (HDPE), linear low density polyethylene (LLDPE), very low density polyethylene (VLDPE), ultra-low density polyethylene (ULDPE), homogeneously branched linear ethylene-based polymers, and homogeneously branched substantially linear ethylene-based polymers (i.e., homogeneously branched long chain branched ethylene polymers). Suitable propylene-based polymers include, but are not limited to, polypropylene homopolymers and propylene / ethylene copolymers.
[0161] The inventive composition may comprise a combination of two or more embodiments as described herein. The ethylene / α-olefin interpolymer may comprise a combination of two or more embodiments as described herein. The peroxide may comprise a combination of two or more embodiments as described herein. The "Si-containing compound" may comprise a combination of two or more embodiments as described herein.
[0162] definition
[0163] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.
[0164] As used herein, the term "composition" includes mixtures of materials including the composition as well as reaction products and decomposition products formed from the composition materials. Any reaction products or decomposition products are typically present in trace or residual amounts.
[0165] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing monomers of the same or different types. Thus, the generic term polymer encompasses the term homopolymer (used to refer to polymers prepared from only one type of monomer, it being understood that trace amounts of impurities may be incorporated into the polymer structure) and the term interpolymer as defined below. Trace amounts of impurities (such as catalyst residues) may be incorporated into and / or within the polymer. Typically, the polymer is stabilized with very low amounts ("ppm" amounts) of one or more stabilizers.
[0166] As used herein, the term "interpolymer" refers to polymers prepared by the polymerization of at least two different types of monomers. The term interpolymer thus includes the term copolymer (used to refer to polymers prepared from two different types of monomers) and polymers prepared from more than two different types of monomers.
[0167] As used herein, the term "propylene-based polymer" refers to a polymer that comprises, in polymerized form, a majority weight percent propylene (based on the weight of the polymer) and, optionally, may comprise one or more comonomers.
[0168] As used herein, the term "ethylene-based polymer" refers to a polymer that, in polymerized form, comprises 50 wt% or a majority weight percent ethylene (based on the weight of the polymer), and optionally may include one or more comonomers.
[0169] As used herein, the term "ethylene / α-olefin interpolymer" refers to a random interpolymer comprising, in polymerized form, 50 wt % or majority weight percent ethylene (based on the weight of the interpolymer) and an α-olefin.
[0170] As used herein, the term "ethylene / a-olefin copolymer" refers to a random copolymer comprising, in polymerized form, 50 wt% or a major amount of ethylene monomer (based on the weight of the copolymer) and an a-olefin as the only two monomer types.
[0171] As used herein, the term "Si-containing compound" refers to a compound containing at least one "Si" atom and at least one "-CH2-" group and / or at least one "-CH3" group.
[0172] As used herein, the term "solar cell (or photovoltaic cell)" refers to a device that converts solar radiation into electricity. Solar cells are typically presented in an array pattern.
[0173] As used herein, the term "solar cell module (or solar panel or solar module)" refers to a photovoltaic panel that includes an assembly of solar cells.
[0174] As used herein, the terms "laminating," "lamination," and like terms refer to a process in which multiple layers of materials are bonded together under heat and pressure, and optionally, a vacuum.
[0175] The terms "comprising," "including," "having," and derivatives thereof are not intended to exclude the presence of any additional components, steps, or procedures, whether or not the components, steps, or procedures are specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequently recited component, step, or procedure, except those that are not essential to operability. The term "consisting of excludes any component, step, or procedure not specifically recited or listed.
[0176] List of some composition features
[0177] A] A composition comprising:
[0178] a) ethylene / α-olefin / interpolymer;
[0179] b) peroxides;
[0180] c) "Si-containing compounds" selected from the following i) to v):
[0181] i)
[0182] Wherein each R is independently selected from C1-C3 alkyl or C1-
[0183] C2 alkyl or C1 alkyl; and n is 1 to 16, or 1 to 14, or 1 to 12, or 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4;
[0184] ii)
[0185] wherein each R is independently methyl or ethyl or methyl; and n is 1 to 18, or 1 to 16, or 1 to 14, or 1 to 12, or 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4, or 1 to 3;
[0186] iii)
[0187] wherein each R is independently methyl or ethyl or ethyl;
[0188] iv) vinyl oligosiloxane; or
[0189] v) Any combination of i) to iv).
[0190] B] A composition according to A] above, wherein the "Si-containing compound" (component c) is selected from
[0191] i) to v) below:
[0192] i)
[0193]
[0194] ii)
[0195]
[0196] iii)
[0197]
[0198] iv) vinyl oligosiloxane, or v) any combination of i) to iv).
[0199] C] A composition according to A] above, wherein the "Si-containing compound" is selected from the following:
[0200] iv) Vinyl oligosiloxane.
[0201] D] A composition according to C] above, wherein the "Si-containing compound" is a compound comprising at least two
[0202] Different vinyl oligosiloxanes selected from the following compounds of Formula 4A:
[0203] iv) R1 x R2 y R3 z Si n O m(Formula 4A), where R1 is vinyl, x is greater than or equal to (≥) 1, R2 is propyl, y is greater than or equal to (≥) 0 and less than or equal to (≤) 1, R3 is ethoxy or methoxy, z = 4n - x - y - m, 1 < n < 10, and m ≤ n - 1. E] The composition according to A] above, wherein the "Si-containing compound" is selected from the following:
[0204] i)
[0205] where each R is independently selected from C1-C3 alkyl or C1-C2 alkyl or C1 alkyl; and n is from 1 to 16, or from 1 to 14, or from 1 to 12, or from 1 to 10, or from 1 to 8, or from 1 to 6, or from 1 to 4;
[0206] ii)
[0207] where each R is independently methyl or ethyl or methyl; and n is from 1 to 18, or from 1 to 16, or from 1 to 14, or from 1 to 12, or from 1 to 10, or from 1 to 8, or from 1 to 6, or from 1 to 4, or from 1 to 3;
[0208] iii)
[0209] where each R is independently methyl or ethyl or ethyl; or
[0210] v) Any combination of i) to iii).
[0211] F] The composition according to E] above, wherein the "Si-containing compound" (component c) is selected from the following i) to v):
[0212] as follows:
[0213] i)
[0214]
[0215] ii)
[0216]
[0217] iii)
[0218] or v) Any combination of i) to iii).
[0219] G] The composition according to A] above, wherein the "Si-containing compound" is selected from the following:
[0220] ii)
[0221] wherein each R is independently methyl or ethyl or methyl; and n is 1 to 18, or 1 to 16, or 1 to 14, or 1 to 12, or 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4, or 1 to 3;
[0222] iii)
[0223] wherein each R is independently methyl or ethyl or ethyl;
[0224] v) A combination of ii) and iii).
[0225] H] A composition according to G] above, wherein the "Si-containing compound" is selected from the following: Or a combination of v) ii) and iii).
[0226] I] A composition according to G] or H] above, wherein the "Si-containing compound" is selected from ii) and
[0227] iii).
[0228] J] A composition according to any one of G]-I] (G to I) above, wherein component iii) and
[0229] The weight ratio of component ii) is ≥2.0, or ≥2.2, or ≥2.4, or ≥2.6, or ≥2.8, or ≥3.0.
[0231] K] A composition according to any one of G] to J] above, wherein the weight of component iii) and component ii) is
[0232] The amount ratio is ≤4.0, or ≤3.8, or ≤3.6, or ≤3.4, or ≤3.2.
[0233] L] A composition according to A] above, wherein the "Si-containing compound" is selected from the following:
[0234] i)
[0235] wherein each R is independently selected from C1-C3 alkyl or C1-C2 alkyl or C1 alkyl; and n is 1 to 16, or 1 to 14, or 1 to 12, or 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4.
[0236] M] A composition according to L) above, wherein the "Si-containing compound" is selected from the following:
[0237] i)
[0238]
[0239] N] The composition according to A] above, wherein the "Si-containing compound" is selected from the following:
[0240] ii)
[0241] wherein each R is independently methyl or ethyl or methyl; and n is 1 to 18, or 1 to 16, or 1 to 14, or 1 to 12, or 1 to 10, or 1 to 8, or 1 to 6, or 1 to 4, or 1 to 3.
[0242] O] The composition according to N] above, wherein the "Si-containing compound" is selected from the following:
[0243] ii)
[0244]
[0245] P] A composition according to A] above, wherein the "Si-containing compound" is selected from the following:
[0246] iii)
[0247] wherein each R is independently methyl or ethyl or ethyl;
[0248] Q] A composition according to P] above, wherein the "Si-containing compound" is selected from the following:
[0249]
[0250] R] A composition according to any one of A]-Q] (A to Q) above, wherein the composition further
[0251] Contains a crosslinking aid.
[0252] S] A composition according to R] above, wherein the composition comprises ≥
[0253] 0.05wt%, or ≥0.10wt%, or ≥0.15wt%, or ≥0.20wt% of a cross-linking aid.
[0254] T] A composition according to R] or S] above, wherein the composition comprises by weight of the composition
[0255] ≤1.50wt%, or ≤1.40wt%, or ≤1.30wt%, or ≤1.20wt%, or ≤
[0256] 1.10wt%, or ≤1.00wt% of a cross-linking aid.
[0257] U] A composition according to any one of R] to T] above, wherein the auxiliary agent is as follows:
[0258]
[0259] V] A composition according to any one of R] to U] above, wherein the weight of the peroxide and the auxiliary agent is
[0260] The amount ratio is ≥0.5, or ≥0.8, or ≥1.0, or ≥1.2, or ≥1.4, or ≥1.6, or ≥
[0261] 1.8, or ≥2.0.
[0262] W] A composition according to any one of R] to V] above, wherein the weight of the peroxide and the auxiliary agent is
[0263] The amount ratio is ≤3.0, or ≤2.8, or ≤2.6, or ≤2.4, or ≤2.2.
[0264] X] A composition according to any one of A] to W] above, wherein the composition comprises ≥0.01 wt%, or ≥0.02 wt%, or ≥0.04 wt%, or ≥0.06 wt% based on the weight of the composition.
[0265] wt%, or ≥ 0.08wt%, or ≥ 0.10wt% of "Si-containing compound".
[0266] Y] A composition according to any one of A] to X] above, wherein the composition comprises ≤1.00wt%, or ≤0.80wt%, or ≤0.60wt%, or ≤0.40wt% of "Si-containing compound" based on the weight of the composition.
[0267] Z] A composition according to any one of A] to Y] above, wherein the peroxide and the "Si-containing compound"
[0268] The weight ratio of the "compound" is ≥1.0, or ≥1.5, ≥2.0, or ≥2.2, or ≥2.4, or ≥
[0269] 2.6, or ≥2.8, or ≥3.0, or ≥3.2, or ≥3.4, or ≥3.6, or ≥3.8, or ≥4.0.
[0271] AA] A composition according to any one of A] to Z] above, wherein the weight ratio of peroxide to "Si-containing compound" is ≤6.0, or ≤5.8, or ≤5.6, or ≤5.4, or ≤5.2, or ≤5.0, or ≤4.8, or ≤4.6, or ≤4.4, or ≤4.2.
[0272] BB] A composition according to any one of A] to AA] above, wherein the composition comprises ≥0.1 wt%, or ≥0.2 wt%, or ≥0.4 wt%, or ≥0.6 wt% based on the weight of the composition.
[0273] wt%, or ≥0.8wt%, or ≥1.0wt% of peroxide.
[0274] CC] A composition according to any one of A] to BB] above, wherein the composition comprises ≤3.0wt%, or ≤2.8wt%, or ≤2.6wt%, or ≤2.4wt%, or ≤2.2wt%, or ≤2.0wt% peroxide based on the weight of the composition.
[0275] DD] A composition according to any one of A] to CC] above, wherein the peroxide is selected from the following:
[0276]
[0277] EE] A composition according to any one of A] to DD] above, wherein the composition further comprises a hindered amine.
[0278] FF) A composition according to EE] above, wherein the hindered amine is as follows:
[0279]
[0280] GG] A composition according to EE] or FF] above, wherein the weight ratio of the "Si-containing compound" to the hindered amine is ≥1.0, or ≥2.0, or ≥3.0, or ≥3.1, or ≥3.2, or ≥
[0281] 3.3, or ≥3.4, or ≥3.5.
[0282] HH] A composition according to any one of EE] to GG] above, wherein the "Si-containing compound"
[0283] The weight ratio to the hindered amine is ≤7.0, or ≤6.8, or ≤6.6, or ≤6.4, or ≤6.2, or ≤6.0.
[0284] II] A composition according to any one of A] to HH] above, wherein the composition comprises ≥50.0 wt%, or ≥60.0 wt%, or ≥70.0 wt%, or ≥80.0 wt% based on the weight of the composition.
[0285] wt%, or ≥ 90.0 wt% of ethylene / α-olefin interpolymer (component a).
[0286] JJ] A composition according to any one of A] to II] above, wherein the composition comprises ≥80.0wt%, or ≥82.0wt%, or ≥84.0wt%, or ≥86.0wt% based on the weight of the composition.
[0287] wt%, or ≥ 88.0 wt%, or ≥ 90.0 wt%, or ≥ 92.0 wt%, or ≥ 94.0 wt% of the ethylene / α-olefin interpolymer (component a).
[0288] KK] A composition according to any one of A] to JJ] above, wherein the composition comprises ≥95.0 wt%, or ≥95.5 wt%, or ≥96.0 wt%, or ≥96.5
[0289] wt%, or ≥ 97.0 wt%, or ≥ 97.5 wt%, or ≥ 98.0 wt% of the ethylene / α-olefin interpolymer (component a).
[0290] LL] A composition according to any one of A] to KK] above, wherein the composition comprises ≤99.8wt%, ≤99.6wt%, or ≤99.4wt%, or ≤99.2
[0291] wt%, or ≤99.0wt%, or ≤98.8wt%, or ≤98.6wt%, or ≤98.4
[0292] wt%, or ≤ 98.2 wt% of ethylene / α-olefin interpolymer (component a).
[0293] MM] A composition according to any one of A] to LL] above, wherein the composition comprises ≥98.5%, ≥99.0wt%, or ≥99.1wt%, or ≥99.2wt%, or ≥99.3wt%, or ≥99.4wt% of the sum of components a)-c) based on the weight of the composition.
[0294] NN] A composition according to any one of A] to MM] above, wherein the composition comprises ≤100.0wt%, or ≤99.9wt%, ≤99.8wt%, or ≤99.7wt% based on the weight of the composition.
[0295] wt%, or ≤ 99.6 wt%, or ≤ 99.5 wt% of the sum of components a) - c).
[0296] OO] A composition according to any one of A] to NN] above, wherein for the ethylene / α-olefin interpolymer, the α-olefin is a C3-C20 α-olefin, and further is a C3-C10 α-olefin.
[0297] PP] A composition according to any one of A] to OO] above, wherein for the ethylene / α-olefin interpolymer, the α-olefin is selected from propylene, 1-butene, 1-pentene, 1-hexene or 1-octene, and further propylene, 1-butene or 1-octene, and further 1-butene or 1-octene, and further 1-octene.
[0298] QQ] A composition according to any one of A] to PP] above, wherein the ethylene / α-olefin interpolymer (component a) is an ethylene / α-olefin copolymer.
[0299] RR] A composition according to any one of A] to QQ] above, wherein the ethylene / α-olefin interpolymer (component a) is selected from the following: ethylene / propylene copolymer, ethylene / butene copolymer or ethylene / octene copolymer, and further ethylene / butene copolymer or ethylene / octene copolymer, and further ethylene / octene copolymer.
[0300] SS] A composition according to any one of A] to RR] above, wherein the density of the ethylene / α-olefin interpolymer (component a) is ≥ 0.860 g / cc, ≥ 0.865 g / cc, ≥ 0.870 g / cc, or ≥
[0301] 0.872g / cc, or ≥0.874g / cc, or ≥0.876g / cc, or ≥0.878g / cc, or ≥
[0302] 0.880g / cc(1cc=1cm 3 ).
[0303] TT] A composition according to any one of a] to SS] above, wherein the density of the ethylene / α-olefin interpolymer is ≤ 0.900 g / cc, or ≤ 0.898 g / cc, or ≤ 0.896 g / cc, or ≤
[0304] 0.894g / cc, or ≤0.892g / cc, or ≤0.890g / cc, or ≤0.888g / cc, or ≤
[0305] 0.886 g / cc, or ≤0.884 g / cc, or ≤0.882 g / cc.
[0306] UU] A composition according to any one of A] to TT] above, wherein the melt index (I2) of the ethylene / α-olefin interpolymer (component a) is ≥ 8.0 g / 10 min, or ≥ 10 g / 10 min, or ≥
[0307] VV] A composition according to any one of A] to UU] above, wherein the melt index (I2) of the ethylene / α-olefin interpolymer is ≤35 g / 10 min, ≤30 g / 10 min, or ≤28 g / 10 min.
[0308] min, or ≤26g / 10min, or ≤24g / 10min, or ≤22g / 10min, or ≤
[0309] 20g / 10min.
[0310] WW] A composition according to any one of A] to VV] above, wherein the molecular weight distribution MWD (=Mw / Mn) of the ethylene / α-olefin interpolymer (component a) is ≥1.70, or ≥1.75, or ≥1.80, or ≥1.85, or ≥1.90, or ≥1.95, or ≥2.00.
[0311] XX] A composition according to any one of A] to WW] above, wherein the molecular weight distribution MWD of the ethylene / α-olefin interpolymer is ≤2.70, or ≤2.65, or ≤2.60, or ≤2.55, or ≤2.50, or ≤2.45, or ≤2.40, or ≤2.35, or ≤2.30, or ≤2.25, or
[0312] ≤2.20.
[0313] YY] A composition according to any one of A] to XX] above, wherein the number average molecular weight Mn of the ethylene / α-olefin interpolymer (component a) is ≥ 10,000 g / mol, or ≥
[0314] 12,000g / mol, or ≥14,000g / mol, or ≥16,000g / mol, or ≥
[0315] 18,000 g / mol, or ≥ 20,000 g / mol.
[0316] ZZ] A composition according to any one of A] to YY] above, wherein the number average molecular weight Mn of the ethylene / α-olefin interpolymer is ≤ 50,000 g / mol, or ≤ 45,000 g / mol, or ≤
[0317] 40,000g / mol, or ≤35,000g / mol, or ≤30,000g / mol, or ≤
[0318] 25,000g / mol.
[0319] A3] A composition according to any one of A] to ZZ] above, wherein the weight average molecular weight Mw of the ethylene / α-olefin interpolymer is ≥30,000 g / mol, or ≥35,000 g / mol, or ≥
[0320] 40,000 g / mol, or ≥ 45,000 g / mol.
[0321] B3] A composition according to any one of A] to A3] above, wherein the weight average molecular weight Mw of the ethylene / α-olefin interpolymer is ≤70,000 g / mol, or ≤65,000 g / mol, or ≤
[0322] 60,000 g / mol, or ≤55,000 g / mol.
[0323] C3] A composition according to any one of A] to B3] above, wherein the melting temperature (Tm, DSC) of the ethylene / α-olefin interpolymer (component a) is ≥60°C, or ≥65°C, or ≥70°C, or ≥72°C, or ≥74°C, or ≥76°C, or ≥78°C, or ≥80°C.
[0324] D3] A composition according to any one of A] to C3] above, wherein the melting temperature (Tm, DSC) of the ethylene / α-olefin interpolymer (component a) is ≤100°C, or ≤95°C, or ≤
[0325] 90°C, or ≤88°C, or ≤86°C, or ≤84°C, or ≤82°C.
[0326] E3] A composition according to any one of A] to D3] above, wherein the crystallization temperature (Tc, DSC) of the ethylene / α-olefin interpolymer is ≥40°C, or ≥45°C, or ≥50°C, or ≥52°C, or ≥54°C, or ≥56°C.
[0327] F3] A composition according to any one of A] to E3] above, wherein the ethylene / α-olefin interpolymer has a crystallization temperature (Tc, DSC) of ≤70°C, or ≤68°C, or ≤66°C, or ≤64°C, or ≤62°C, or ≤60°C.
[0328] G3] A composition according to any one of A] to F3] above, wherein the glass transition temperature (Tg, DSC) of the ethylene / α-olefin interpolymer is ≥-70°C, or ≥-65°C, or ≥-60°C, or ≥-58°C, or ≥-56°C, or ≥-54°C, or ≥-52°C, or ≥-50°C.
[0329] H3] A composition according to any one of A] to G3] above, wherein the glass transition temperature (Tg, DSC) of the ethylene / α-olefin interpolymer is ≤-30°C, or ≤-35°C, or ≤-38°C, or ≤-40°C, or ≤-42°C, or ≤-44°C, or ≤-46°C.
[0330] I3] A composition according to any one of A] to H3] above, wherein the composition comprises <0.002 wt%, or <0.001 wt%, or <0.0005 wt% titanium dioxide based on the weight of the composition.
[0331] J3] A composition according to any one of A] to I3] above, wherein the composition does not contain titanium dioxide.
[0332] K3] A composition according to any one of A] to J3] above, wherein the composition comprises <0.002 wt%, or <0.001 wt%, or <0.0005 wt% of magnesium hydroxide based on the weight of the composition.
[0333] L3] A composition according to any one of A] to K3] above, wherein the composition does not contain magnesium hydroxide.
[0334] M3] A composition according to any one of A] to L3] above, wherein the composition comprises <0.002wt%, or <0.001wt%, or <0.0005wt% magnesium oxide based on the weight of the composition.
[0335] N3] A composition according to any one of A] to M3] above, wherein the composition does not contain magnesium oxide.
[0337] O3] A composition according to any one of A] to N3] above, wherein the composition comprises <0.002wt%, or <0.001wt%, or <0.0005wt% of polymer microspheres (such as cross-linked polymer microspheres) based on the weight of the composition.
[0338] P3] A composition according to any one of A] to O3] above, wherein the composition does not contain polymer microspheres (such as cross-linked polymer microspheres).
[0339] Q3] A cross-linked composition formed from the composition according to any one of A] to P3] above.
[0340] R3] A composition according to any one of A] to Q3] above, wherein the glass adhesion strength of the composition is ≥90 N / cm, or ≥92 N / cm, or ≥94 N / cm, or ≥96 N / cm. S3] A composition according to any one of A] to R3] above, wherein the glass adhesion strength of the composition is ≥100 N / cm, or ≥110 N / cm, or ≥120 N / cm, or ≥130
[0341] N / cm, or ≥140N / cm.
[0342] T3] A composition according to any one of a] to S3] above, wherein the composition is heated to 85°C,
[0343] The glass adhesion strength after aging for 1000h at 85% humidity is ≥70N / cm, or ≥75
[0344] N / cm, or ≥80N / cm, or ≥85N / cm, or ≥90N / cm, or ≥95N / cm, or ≥100N / cm, or ≥105N / cm.
[0345] U3] A composition according to any one of A] to T3] above, wherein the composition is heated to 85°C,
[0346] The glass adhesion strength after aging for 1000h at 85% humidity is ≥50%, or ≥55%, or
[0347] ≥60%, or ≥65%, or ≥70%.
[0348] V3] A composition according to any one of A] to U3] above, wherein the volume resistivity of the composition is ≥1.0×10 14 ohm·cm, or ≥5.0×10 15 ohm·cm, or ≥2.0×10 16
[0349] ohm·cm, or ≥2.5×10 16 ohm·cm, or ≥3.0×10 16 ohm·cm, or ≥4.0
[0350] ×10 16 ohm·cm, or ≥5.0×10 16 ohm·cm.
[0351] W3] A composition according to any one of A] to V3] above, wherein the volume resistivity of the composition is ≥1.0×10 17 ohm·cm, or ≥1.2×10 17 ohm·cm, or ≥1.4×10 17
[0352] ohm·cm, or ≥1.6×10 17 ohm·cm, or ≥1.8×10 17 ohm·cm, or ≥1.9
[0353] ×10 17 ohm·cm.
[0354] X3] A composition according to any one of A] to W3], wherein the volume resistivity of the composition is ≤
[0355] 1×10 19 ohm·cm.
[0356] Y3] An article comprising at least one component formed from the composition according to any one of A] to X3] above.
[0357] Z3] The article according to Y3] above, wherein the article is a film, and further is an extruded film.
[0358] A4] An article according to Y3] or Z3] above, wherein the article is a film comprising ≤ 2 layers, and is another layer.
[0359] B4] The article according to Y3] above, wherein the article is a solar cell module.
[0360] C4] A method of forming a solar cell module, the method comprising laminating a solar cell array between two film layers, and wherein each film layer is independently formed from a composition as described in any one of A] to X3] above.
[0361] D4] The method according to C4] above, wherein each film layer is formed from the same composition.
[0362] Test Method
[0363] MDR Testing
[0364] According to ASTM D5289, the curing characteristics were measured using an Alpha Technology Moving Die Rheometer (MDR) 2000E at a 0.5 degree arc. The MDR was loaded with 5 g of each uncured polymer composition (extruded film) and run at a temperature of 145°C for 30 minutes to generate a "time versus torque" curve for the composition within a given interval. The following data were used from each MDR test: a) MH (dNm): the maximum torque applied by the MDR during the 30 minute test interval (this generally corresponds to the torque applied at 30 minutes); and b) t90 or the time to reach 90% MH value.
[0365] Glass Adhesion Test
[0366] Each laminate sample was cut into three specimens, each with a width of "one inch" (see Figure 1 (Chinese)). Figure 1 As shown in (right), the glass adhesion strength was measured using a 180° peel test (average glass adhesion strength was 1" to 2"). The test was performed on an INSTRON™ 5565 under controlled environmental conditions. Six samples were tested and the results were averaged. The initial strength and the strength after aging for 1000 hours at a temperature of 85°C and 85% humidity (wet heat aging test) were recorded, and the retention ratio was calculated.
[0367] Volume resistivity test
[0368] The volume resistivity test is based on ASTM D257. The measurements are performed using a KEITHLEY 6517B electrometer in combination with a KEITHLEY 8009 test fixture. The leakage current is read directly from the instrument and used in the following equation to calculate the volume resistivity:
[0369]
[0370] Where ρ is the volume resistivity (ohm cm), V is the applied voltage (volts), and A is the electrode contact area (cm 2 ) and I is the leakage current (amperes). The thickness (t) of the cured film prepared by compression molding was measured before testing. Five points on the compression molded film were measured to obtain an average "t value", and this value was incorporated into the above equation to determine the volume resistivity. The test was conducted at 1000 volts and room temperature. For each composition, the average volume resistivity of two compression molded films was tested.
[0371] Melt Index
[0372] The melt index (I2) of the ethylene-based polymer is measured according to ASTM D-1238 at 190°C / 2.16kg (melt index (I5) is measured at 190°C / 5.0kg, melt index (I10) is measured at 190°C / 10.0kg, and high load melt index (I21) is measured at 190°C / 21.0kg). The melt flow rate (MFR) of the propylene-based polymer is measured according to ASTM D-1238 at 230°C / 2.16kg.
[0373] Polymer density
[0374] Polymer density is measured according to ASTM D-792.
[0375] Gel Permeation Chromatography
[0376] The chromatographic system consists of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment is set at 160°C and the column compartment is set at 150°C. The column is four Agilent "Mixed A" 30cm 20 micron linear mixed bed chromatographic columns. The chromatographic solvent is 1,2,4-trichlorobenzene containing 200ppm of butylated hydroxytoluene (BHT). The solvent source is nitrogen sparged. The injection volume used is 200 microliters, and the flow rate is 1.0 ml / min.
[0377] The GPC column set was calibrated with 21 narrow molecular weight distribution polystyrene standards, ranging in molecular weight from 580 to 8,400,000, and arranged in six "cocktail" mixtures, with at least ten times the interval between individual molecular weights. Standards were purchased from Agilent Technologies. For molecular weights equal to or greater than 1,000,000, 0.025 grams of polystyrene standards were prepared in 50 milliliters of solvent, and for molecular weights less than 1,000,000, 0.05 grams of polystyrene standards were prepared in 50 milliliters of solvent. The polystyrene standards were gently stirred at 80 degrees Celsius for 30 minutes to dissolve. The polystyrene standard peak molecular weight was converted to polyethylene molecular weight using equation 1 (as described in Williams and Ward, Journal of Polymer Science (J. Polym. Sci.), Polym. Let., 6, 621 (1968)):
[0378] M polyethylene =A×(M polystyrene ) B (EQ1), where M is the molecular weight, A has a value of 0.4315, and B equals 1.0.
[0379] A fifth order polynomial was used to fit the calibration points to the corresponding polyethylene equivalents.A small adjustment (approximately 0.375 to 0.445) was made to A to correct for column resolution and band broadening effects such that a linear homopolymer polyethylene standard was obtained at 120,000 Mw.
[0380] Plate counts for the GPC column set were performed using decane (prepared as 0.04 g in 50 mL TCB and dissolved for 20 minutes under slow stirring). Plate counts (Equation 2) and symmetry (Equation 3) were measured at 200 μL injection according to the following equations:
[0381] Where RV is the retention volume in milliliters, peak width is in milliliters, peak maximum is the maximum height of the peak, and 1 / 2 height is 1 / 2 the height of the peak maximum.
[0382] Where RV is the retention volume in milliliters, and peak width is in milliliters, peak maximum is the maximum peak position, tenth height is 1 / 10 the height of the peak maximum, and where post-peak refers to the tail of the peak at a later retention volume than the peak maximum, and where pre-peak refers to the front of the peak at an earlier retention volume than the peak maximum. The plate count of the chromatographic system should be greater than 18,000, and the symmetry should be between 0.98 and 1.22.
[0383] The samples were prepared semi-automatically using the PolymerChar "Instrument Control" software, where the target weight of the sample was set to 2 mg / ml, and the solvent (containing 200 ppm BHT) was added to a septum-covered vial previously sparged with nitrogen by a PolymerChar high temperature autosampler. The samples were dissolved at 160 degrees Celsius for two hours under "slow" shaking.
[0384] Based on the GPC results, the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR spectrometer was used, according to Equations 4-6, using the PolymerChar GPCOne TM The software was used to calculate the Mn of the baseline-subtracted IR chromatogram at each equidistant data collection point (i) and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) according to Equation 1. (GPC) 、Mw (GPC) and Mz (GPC) Calculation of. Equation 4-6 is as follows:
[0385]
[0386] To monitor the deviation over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by a PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (nominal)) of each sample by comparing the RV of the corresponding decane peak in the sample (RV (FM sample)) with the RV of the alkane peak in the narrow standard calibration (RV (calibrated through FM)). It was then assumed that any change in the time of the decane marker peak was related to a linear change in the flow rate (flow rate (effective)) of the entire run. In order to facilitate the highest accuracy of the RV measurement of the flow marker peak, the peak of the flow marker concentration chromatogram was fitted to a quadratic equation using a least squares fitting procedure. The first derivative of the quadratic equation was then used to solve for the true peak position. After calibrating the system based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated by equation 7 (FM 7): flow rate (effective) = flow rate (nominal) * (RV (calibrated through FM) / RV (FM sample)) (EQ7).
[0387] By PolymerCharGPCOne TM The software completes the processing of the flow marker peaks. An acceptable flow rate correction is such that the effective flow rate should be within + / - 2% of the nominal flow rate.
[0388] Differential Scanning Calorimetry (DSC)
[0389] Differential scanning calorimetry (DSC) is used to measure Tm, Tc, Tg and crystallinity in ethylene (PE) samples and propylene (PP) samples. Each sample (0.5g) is compression molded into a film at 5000psi, 190°C for two minutes. About 5 to 8mg of the film sample is weighed and placed in a DSC pan. The lid is screwed on the pan to ensure a closed atmosphere. The sample pan is placed in a DSC unit and then heated to a temperature of 180°C for PE (for PP, heated to 230°C) at a rate of about 10°C / min. The sample is kept at this temperature for three minutes. Then, the sample is cooled to -90°C (for PP, cooled to -60°C) at a rate of 10°C / min for PE, and isothermally kept at the temperature for three minutes. The sample is then heated at a rate of 10°C / min until fully melted (second heating). Unless otherwise stated, the melting point (Tm) and glass transition temperature (Tg) of each polymer are determined from the second heating curve, and the crystallization temperature (Tc) is determined from the first cooling curve. The corresponding peak temperatures of Tm and Tc are recorded. The percentage of crystallinity can be calculated by dividing the heat of fusion (Hf) determined from the second heating curve by the theoretical heat of fusion of 292 J / g for PE (for PP, 165 J / g) and multiplying this number by 100 (e.g., % crystallinity = (Hf / 292 J / g) × 100 (for PE)).
[0390] experiment
[0391] Polymers and Additives
[0392] Ethylene / 1-octene random copolymer: density 0.880 g / cc, I2 18.0 g / 10 min, Mn 22951 g / mol, MWD 2.16, Tm 81°C, Tc 57°C, Tg -47°C (e.g., XUS 38661 from The Dow Chemical Company). This copolymer is denoted "POE" in the following table.
[0393] Tert-butyl carbonate (referred to as "TBEC" in the following table): organic peroxide (eg, from J&K Scientific Ltd.).
[0394] 5-Hexenyltrimethoxysilane (referred to as "SC1" in the following table): Si-containing compound (eg, DOWSIL Z-6161EX Silane from The Dow Chemical Company).
[0395] Trimethoxysilylpropanethiol (referred to as "SC2" in the following table): Si-containing compound (eg, XIAMETER OFS-6062 from The Dow Chemical Company).
[0396] Tetraethyl orthosilicate (indicated as "SC3" in the following table): Si-containing compound (eg, XIAMETER 6697 from The Dow Chemical Company).
[0397] Vinyl oligosiloxane (referred to as "SC4" in the following table): Si-containing compound (eg DYNASYLAN 6598 from EVONIK).
[0398] 3-(Trimethoxysilyl)propyl methacrylate (denoted as "SCC" in the following table): Si-containing compound (eg, XIAMETER OFS-6030 from The Dow Chemical Company).
[0399] Triallyl isocyanurate (indicated as "TAIC" in the following table): a cross-linking auxiliary agent (eg from Fangruida Chemicals Co., Ltd).
[0400] Bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate (denoted as "T770" in the table below): hindered amine light stabilizer (eg, TINUVIN 770 from BASF).
[0401] Back film: ZTT-KPE (PVDF / PET / PEVA), which can be purchased from Zhongtian Photovoltaic Materials Co., Ltd.
[0402] Polymer composition
[0403] Inventive and comparative compositions were prepared according to the formulations listed in Table 1. The comparative compositions represent inventive compositions for photovoltaic encapsulation films.
[0404] Table 1: Polymer composition
[0405]
[0406] For each polymer composition, the organic peroxide, Si-containing compound, crosslinking aid and POE resin (pellets) were weighed in the desired percentages and premixed into sealable bottles. The bottle and its contents were shaken for one minute and then placed in an oven at 40°C for equilibrium to soak the additives in the POE resin. For the first 60 minutes in the oven, the bottle was shaken every 10 minutes to maintain uniform distribution of the cured package. After the 60-minute interval, the bottle was kept in a 40°C oven for 15-20 hours (overnight).
[0407] Film extrusion
[0408] The pellets after soaking were fed into a BRABENDER single screw extruder with three barrels. The temperature of each barrel and the temperature of the die were set to 100°C, and the screw speed was 40 rpm. Approximately "0.5 mm thick POE extruded film" was prepared and then kept in an aluminum foil bag for testing.
[0409] Compression molding
[0410] The extruded film (POE film) was cured during the compression molding process. The extruded film was preheated at 120°C for five minutes, then degassed, and then subjected to a 15-minute pressing process at 150°C at 10 MPa to ensure complete curing of the sample. The temperature was then cooled to room temperature. The compression molded film was used for volume resistivity testing.
[0411] laminated
[0412] For each sample, a glass substrate (4 inches × 6 inches × 0.12 inches (thick)) was used. The substrate was cleaned with water and then dried before use. The bottom film with a thickness of 0.35 mm was cut into "4×6 square inches" small pieces. The extruded film (POE film) was cut to fit the size of the glass and the size of the bottom film, respectively. Before lamination, the bottom film, extruded film and glass were stacked together (from top to bottom: bottom film, POE film and glass). The lamination process was carried out on a PENERGY L036 laminator at 150°C for 20 minutes (4 minutes of vacuum process (vacuum pressure-0.095 MPa) and 16 minutes of pressing (pressure pressure 0.075 MPa)) to form a "glass-film-bottom film" laminate. The thickness of the laminate ranged from 3.9 mm to 4.0 mm. The laminated samples were used for glass adhesion testing.
[0413] Test Results
[0414] The curing, volume resistivity and adhesion properties are shown in Table 2.
[0415] Table 2: Properties of comparative examples and examples of the present invention
[0416]
[0417] It has been found that the compositions of the present invention provide acceptable glass adhesion strength before and after aging. The crosslinking aid also promotes the curing of these compositions. Inventive Example 1 with SC1 as the Si-containing compound maintains higher glass adhesion after aging for 1000 hours at 85°C and 85% humidity (wet heat aging test) compared to the comparative examples with SCC as the Si-containing compound. The inventive examples have good volume resistivity (VR). The T90 of the inventive samples is slightly shorter than the T90 of the comparative samples, indicating that "SC1" provides a slight increase in cure rate while sacrificing torque after cure.
[0418] Compared to the comparative example, Example 2 of the present invention having SC2 as the Si-containing compound also maintains higher glass adhesion after the wet heat aging test. The present example also has excellent initial glass adhesion and good volume resistivity. However, the T90 of Example 2 of the present invention is longer than the T90 of the comparative sample, and the MH is lower than the MH of the comparative example. It is speculated that the thiol group of SC2 reacts with the peroxide, resulting in a lower degree of crosslinking, i.e., a lower MH. By reducing the dosage of SC2 and adding some SC3 to the formulation, the glass adhesion properties and the curing behavior can be balanced, as seen in Example 3 of the present invention. Example 3 of the present invention has excellent initial glass adhesion and maintains glass adhesion after aging tests, as well as excellent volume resistivity. Example 4 of the present invention having SC4 as the Si-containing compound also has excellent initial glass adhesion and maintains glass adhesion after aging tests. This example has excellent volume resistivity.
[0419] The polymer compositions have been found to provide good adhesion to glass and excellent retention of such glass adhesion, which is one of the most important performance characteristics required of photovoltaic encapsulation films. These compositions also have a high cross-linking rate and a high volume resistivity.
Claims
1. A membrane or module comprising a composition comprising: a) 50.0 wt% to 99.8 wt% of an ethylene / α-olefin interpolymer; b) 0.1 wt % to 3.0 wt % of a peroxide; c) 0.1 wt% to 1 wt% of a "Si-containing compound" selected from the following i) to v): i) wherein each R is independently selected from C1-C3 alkyl, and n is 1 to 16; ii) wherein each R is independently methyl or ethyl, and n is 1 to 18; iii) wherein each R is independently methyl or ethyl; v) Any combination of i) to iv).
2. The membrane or module according to claim 1, wherein the "Si-containing compound" is selected from the following: iv) Vinyl oligosiloxane.
3. The membrane or module according to claim 2, wherein the "Si-containing compound" is a vinyl oligosiloxane comprising at least two different compounds selected from the following formula 4A: iv) R1 x R2 y R3 z Si n O m (Formula 4A), where R1 is vinyl, x is greater than or equal to (≥) 1, R2 is propyl, y is greater than or equal to (≥) 0 and less than or equal to (≤) 1, R3 is ethoxy or methoxy, z = 4n - x - y - m, 1 < n < 10, and m ≤ n - 1.
4. The membrane or module according to claim 1, wherein the "Si-containing compound" is selected from the following: ii) wherein each R is independently methyl or ethyl, and n is 1 to 18; iii) wherein each R is independently methyl or ethyl; or v) A combination of ii) and iii).
5. The membrane or module according to claim 4, wherein the "Si-containing compound" is selected from the following: or vi) A combination of ii) and iii).
6. A membrane or module according to claim 4 or claim 5, wherein the "Si-containing compound" is selected from the combination of ii) and iii).
7. The membrane or module according to claim 6, wherein the weight ratio of component iii) to component ii) is ≥ 2.
0.
8. The membrane or module according to claim 6, wherein the weight ratio of component iii) to component ii) is ≤ 4.
0.
9. The membrane or module according to claim 1, wherein the "Si-containing compound" is selected from the following: i) wherein each R is independently selected from C1-C3 alkyl, and n is 1 to 16.
10. The film or module according to any one of claims 1 to 5, wherein the composition has a glass adhesion strength of ≥ 70 N / cm after aging at 85°C and 85% humidity for 1000 h.
